Identification of endophytic fungi of Ageratina pichinchensis with antagonistic activity against phytopathogens of agricultural importance - Camacho-Luna, Valeria; Rodríguez-Hernández, Aida Araceli; Rodríguez-Monroy, Mario; Robledo, Norma; Sepúlveda-Jiménez, Gabriela (Revista Mexicana de Ciencias Agrícolas, 2022)
Ageratina pichinchensis is a medicinal plant, endemic to Mexico, known as Axihuitl. The extracts of the leaves show antifungal activity against dermatophytic fungi, but there are no studies of the identification of endophytic fungi. The objective was to identify endophytic fungi of A. pichinchensis with potential as biological control agents of phytopathogens. Fifty-five morphospecies of endophytic fungi that belong to the phylum Ascomycota were isolated from the leaves of A. pichinchensis. Molecular identification based on the analysis of the sequences of internal transcribed spacers (ITSs) amplified by PCR showed that six of the most frequent fungi correspond to Remotididymella anthropophila and Diaporthe caatingaensis and to the genera Diaporthe, Phomopsis and Fusarium. In multiple antagonism assays, seven morphospecies showed strong antagonistic activity against the pathogens Fusarium oxysporum, F. proliferatum and Stemphylium vesicarium. Two endophytic fungi belong to Alternaria alternata, another to Trichoderma longibrachiatum and two others are from the genera Alternaria and Phomopsis. While Nigrospora oryzae was the only most frequent endophyte and with antagonistic activity against the three pathogens. In dual culture assays, endophytes with strong antagonistic activity inhibited the mycelial growth of F. oxysporum and F. proliferatum by 37 to 80%, but in the poisoned food assay, T. longibrachiatum inhibited the mycelial growth of the two pathogens by 79% and 66%, respectively. For the first time, R. anthropophila as an endophytic fungus, as well as the identification and antagonistic activity of endophytic fungi of A. pichinchensis, are reported.
Keywords: Fusarium; Nigrospora; Remotididymella; Trichoderma; biocontrol